Silicon-carbon negative electrode material with gradient silicon concentration for lithium-ion batteries and preparation method

By using a graded porous carbon structure and carbon cladding with gradient distribution of silicon concentration in silicon carbon anode material, the problems of low porosity utilization rate and slow lithium ion transmission kinetics under silicon-rich systems are solved, and higher cycling performance and energy density are achieved.

CN119764388APending Publication Date: 2025-04-04BERZELIUS (HEFEI) CO LTD +1

Patent Information

Application Number
CN202411948560.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

Smart Images

  • Figure CN119764388A_ABST
    Figure CN119764388A_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries and a preparation method thereof. The silicon-carbon negative electrode material comprises graded porous carbon, nano-silicon and a coating layer. The graded porous carbon comprises an inner core porous carbon and an outer layer porous carbon. The pores of the inner core porous carbon are micropores, and the pores of the outer layer porous carbon are mesopores. Nano-silicon is distributed on the graded porous carbon in a gradient manner to form a silicon-carbon composite. The silicon concentration in the mesopores of the outer layer porous carbon is less than the silicon concentration in the micropores of the inner core porous carbon. The coating layer is a carbon layer, which is coated on the surface of the silicon-carbon composite. This gradient distribution of silicon concentration can effectively limit the volume expansion of silicon during battery cycling, reduce side reactions with electrolytes, and avoid the problem of silicon shells being easily generated on the porous carbon surface in a silicon-rich system. In addition, the dense carbon film on the outermost layer of the silicon-carbon negative electrode material further reduces the specific surface area of ​​the material and reduces the formation of SEI film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery negative electrode materials, and in particular relates to a silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries and a preparation method thereof. Background Art

[0002] In order to meet the wide application of portable electronic devices and electric vehicles, there is an urgent need for high energy density lithium-ion batteries. Silicon has a very high theoretical specific capacity (4200mAh g -1 ), a relatively low voltage platform (≈0.4V vsLi / Li + ) and abundant reserves, it is regarded as one of the most promising negative electrode materials for lithium-ion batteries. However, silicon undergoes a huge volume expansion (>300%) during lithium removal and lithium insertion, resulting in mechanical fracture and crushing of the material structure. The unstable formation of the solid electrolyte interface (SEI) caused by repeated volume changes can lead to rapid capacity decay. In addition, the poor conductivity limits its rate performance and electron transferability. In order to solve the above problems, it is crucial to design silicon-based composite materials with high mechanical strength structure and high conductivity to improve the cycling performance of silicon negative electrodes.

[0003] The porous carbon skeleton is considered to be an ideal buffer matrix for nano-silicon due to its large specific surface area, high porosity, good elasticity and high mechanical strength. The presence of micropores increases the accessibility of the ion pair structure, buffers the embedding stress of lithium ions, and is conducive to the rapid diffusion and cycle stability of ions. Therefore, the use of vapor deposition to embed silicon nanoparticles in a porous carbon substrate to prepare silicon-carbon negative electrode materials is considered to be an effective modification strategy. The porous carbon substrate not only enhances the electronic conductivity of the silicon negative electrode, but also acts as a structural buffer to adapt to the volume expansion of silicon. In addition, further coating a dense carbon layer on the surface of the silicon-carbon negative electrode material can effectively reduce the specific surface area of ​​the material, reduce the formation of SEI, and improve the first efficiency of the battery.

[0004] The pore structure of porous carbon, such as pore size, porosity and pore volume, plays a crucial role in determining the electrochemical performance of silicon / carbon porous composite materials. However, the single pore structure of conventional porous carbon is difficult to adapt to the silicon-rich system, because the internal pore structure of conventional porous carbon is difficult to be fully utilized. In a highly permeable silicon system, silicon often cannot be completely deposited inside the porous carbon, but will be deposited outside the porous carbon to form a silicon shell. The formation of the silicon shell will first lead to a poor coverage of the carbon layer on the surface of the silicon-carbon negative electrode material, and the bare silicon will be more easily exposed to the electrolyte, thereby reacting with the electrolyte, causing a loss of active substances, and a decrease in the first efficiency and capacity of the battery. Secondly, the silicon that "overflows" the surface of the porous carbon loses the restriction of the porous carbon pores, and the volume expansion during the cycle is more serious. During the battery cycle, the thick silicon shell will be severely ruptured, resulting in an unstable SEI film, and ultimately causing a rapid decrease in capacity. In addition, during the repeated lithium ion insertion and extraction process, the large volume change caused by the silicon shell may cause particle breakage, separation of active substances from the electrode, and ultimately accelerate capacity decay. More importantly, in a silicon-rich system, the thickness of the silicon-carbon negative electrode material is often thicker and the lithium ion transmission path is longer, resulting in slow lithium ion transmission kinetics.

[0005] Chinese patent CN117766714A discloses a silicon-carbon negative electrode material with a core-shell structure and a preparation method thereof, wherein a phenolic compound, an aldehyde compound and a metal salt compound are reacted under the conditions of an alkali solution and a catalyst, the product after the reaction is calcined to obtain a metal-doped porous carbon material, and then heat-treated with a silane mixed gas to obtain a metal-doped silicon-carbon material, and finally a carbon source gas is used to coat the surface with carbon to prepare the silicon-carbon negative electrode material with a core-shell structure. This method uses carbon nanotubes and amorphous carbon coated with a material shell to restrain the expansion of silicon, but due to the single pore size distribution of the porous carbon and the low internal pore utilization rate, a silicon shell is easily formed on the porous carbon surface under a silicon-rich system. In addition, due to the lack of a buffer layer between the shell inorganic carbon coating layer and the core silicon-carbon material, under high compaction density battery test conditions, the carbon coating layer may be damaged, resulting in direct contact between the electrolyte and silicon, leading to the generation of side reactions.

[0006] The Chinese patent application publication number CN118841554A discloses a composite multi-level structure carbon material and its preparation method and application. The composite multi-level structure carbon material is a three-layer composite structure, the outer layer is a dense carbon structure layer, the middle layer is a high microporous carbon structure layer, the inner core is a micro-mesoporous composite carbon structure layer, and the electrode active material is loaded in the pore structure of the middle layer and the inner core. However, the multi-level structure carbon material in the patent cannot control the silicon to be mainly deposited in the inner core. During the silane deposition process, silane is preferentially adsorbed in the microporous pores of the outer layer, resulting in a large amount of nano-silicon deposited in the outer layer. At the same time, when a certain amount of nano-silicon is deposited on the outer layer, a large number of pores are blocked, resulting in the internal mesopores cannot be fully utilized, and the internal pore volume of the porous carbon is greatly wasted. Furthermore, since more nano-silicon is distributed on the outer layer, the electrodes prepared from this material are assembled into batteries. After long-term cycles, the outer carbon coating is easily damaged due to cyclic expansion. The high microporous structure of the middle layer is more likely to absorb electrolyte due to the capillary effect. Silicon will be in direct contact with the electrolyte, leading to side reactions and dissolution of active substances.

[0007] The Chinese patent application publication number CN118213508A discloses a silicon-carbon negative electrode material, which comprises a multi-level porous carbon material, silicon nanoparticles dispersed in the pores of the multi-level porous carbon material, and an amorphous carbon layer coated on the surface of the multi-level porous carbon material; the pore structure of the multi-level porous carbon material includes micropores, mesopores and macropores, and the pore volume is 0.4cm 3 / g~1.5cm 3 / g, the volume of micropores accounts for 60% to 92% of the total pore volume. The silicon-carbon negative electrode material can effectively inhibit the aggregation of silicon nanoparticles and reduce stress concentration. However, the pore distribution in this patent is relatively wide, resulting in uneven distribution of nano-silicon at the same depth in the porous carbon. At a higher silicon infiltration concentration, the porous carbon surface is prone to local silicon enrichment, especially the microporous structure on the surface. This local silicon enrichment will have a negative impact on the electrochemical properties of the electrode material.

[0008] A Chinese patent with application publication number CN118825269A discloses a low-expansion silicon carbon using composite porous carbon, and its preparation method and application. This method embeds small-particle porous carbon in resin-based porous carbon to form a composite carbon skeleton, nano-silicon is attached to the pores of the composite carbon skeleton, and the outermost layer is coated with a carbon layer. In this patent, there is a certain space around the small-particle porous carbon, so that after the nano-porous carbon deposits nano-silicon, there is more expansion space during the lithium insertion process, which greatly reduces the expansion rate of the entire particle during the lithium insertion process. However, the gaps between the small-particle porous carbon may cause the separation of the small-particle porous carbon and the carbon skeleton during a long cycle, thereby causing the conductive network to be disconnected and the active substance to be inactivated.

[0009] Therefore, in silicon-rich systems, it is urgent to develop a silicon-carbon negative electrode material in which silicon can be effectively confined inside porous carbon and has fast lithium ion transport kinetics to solve the above problems. Summary of the invention

[0010] In view of the problems in the prior art that in a silicon-rich system, a thick silicon shell is easily formed on the surface of the material and the lithium ion transmission kinetics are slow due to the low pore utilization rate inside the porous carbon, the present invention proposes a silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries and a preparation method thereof.

[0011] To achieve the above purpose, the technical solution provided by the present invention is:

[0012] A silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries comprises graded porous carbon, nano-silicon and a coating layer, wherein the graded porous carbon comprises an inner core porous carbon and an outer layer porous carbon, wherein the pores of the inner core porous carbon are micropores, and the pores of the outer layer porous carbon are mesopores, and the nano-silicon is gradiently distributed on the graded porous carbon to form a silicon-carbon complex, wherein the silicon concentration in the mesopores of the outer layer porous carbon is less than the silicon concentration in the micropores of the inner core porous carbon; and the coating layer is a carbon layer, which is coated on the surface of the silicon-carbon complex.

[0013] Preferably, the carbon layer has a dense structure and a thickness of 10 to 200 nm.

[0014] Preferably, the median particle size of the above-mentioned silicon-carbon negative electrode material is 5-10μm, the specific surface area is 1-20m2 / g, preferably 1-10m2 / g, more preferably 1-5m2 / g, the powder resistivity is 1-10Ω·cm, the mass ratio of nano-silicon is 45% to 57%, preferably 53 to 57%, and the nano-silicon is mainly distributed in the inner core porous carbon.

[0015] Preferably, the above-mentioned graded porous carbon is a graded structure; the outer layer porous carbon structure is loose, and its pores are mesopores; the inner core porous carbon structure is dense, and its pores are micropores; the above-mentioned graded porous carbon has a pore volume of 0.5-2.5cm3 / g, preferably 1.5-2.5cm3 / g, a specific surface area of ​​1000-2500m2 / g, preferably 1800-2400m2 / g, and an average pore diameter of 1.0-2.5nm.

[0016] The present invention also provides a method for preparing the above-mentioned silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries, comprising the following steps:

[0017] 1) stirring an aqueous solution containing a phenolic monomer, an aldehyde monomer and a metal salt under heating conditions to obtain a metal ash-doped precursor phenolic resin seed; continuing to sequentially add an aldehyde monomer, a metal salt, an alkaline catalyst, a surfactant and a phenolic monomer to the aqueous solution, stirring and heating, to obtain a metal ash-doped core-shell structure phenolic resin in which a layer of a metal ash-doped phenolic resin shell layer is further coated on the surface of the original metal ash-doped precursor phenolic resin seed;

[0018] 2) heating and curing the core-shell phenolic resin obtained in step 1) in a non-oxidizing atmosphere to obtain a cured product;

[0019] 3) heating the solidified body obtained in step 2) in a non-oxidizing atmosphere to carbonize it to obtain a carbonized body;

[0020] 4) heating and activating the carbonized body obtained in step 3) in an oxidizing atmosphere to obtain an activated body;

[0021] 5) introducing a silicon-containing compound gas into the activated body obtained in step 4) in a non-oxidizing atmosphere to perform siliconization treatment to obtain a silicon-carbon composite body, and then introducing a carbon source gas to perform carbon coating treatment to obtain a carbon-coated body;

[0022] 6) Screening and demagnetizing the carbon coating obtained in step 5) to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

[0023] In step 1), the phenolic monomer is selected from at least one of phenol, resorcinol, aminophenol, tannic acid, and phloroglucinol; the aldehyde monomer is selected from at least one of formaldehyde, terephthalaldehyde, paraformaldehyde, polyoxymethylene, acetaldehyde, valeraldehyde, benzaldehyde, glutaraldehyde, salicylaldehyde, and furanaldehyde; the metal salt is selected from at least one of soluble salts of alkali metals, alkaline earth metals, and transition metals; when preparing the precursor phenolic resin seed, the heating temperature is 25° C. to 50° C., the heating time is 3-7 hours, the mass ratio of the added phenolic monomer to the aldehyde monomer is 1 to 3.5, and the mass of the metal salt is less than 3% of the mass of the phenolic monomer; the alkaline catalyst is selected from ammonia water, p-phenylenediamine, ethylenediamine, hexamethylenediamine, sodium hydroxide, At least one of hexaalkyltrimethylammonium bromide and Bis-tris; the surfactant is selected from at least one of an ionic surfactant and a non-ionic surfactant; when preparing the core-shell structure phenolic resin, the heating temperature is 70°C-100°C, the heating time is 10-14h, the mass ratio of the phenolic monomer and the aldehyde monomer added continuously is 0.20-0.55, the mass ratio of the alkaline catalyst to the phenolic monomer is 0.2-0.5, the mass of the surfactant is 1%-10% of the mass of the phenolic monomer, and the mass of the metal salt is less than 4% of the mass of the phenolic monomer; the mass of the metal salt added continuously when preparing the core-shell structure phenolic resin is higher than the mass of the metal salt added when preparing the precursor phenolic resin seed.

[0024] In step 2), the non-oxidizing atmosphere is selected from at least one of nitrogen, argon, hydrogen or helium, the temperature of heating and curing is 100° C.-300° C., and the holding time is 10-24 hours.

[0025] In step 3), the non-oxidizing atmosphere is selected from at least one of nitrogen, argon, hydrogen or helium; the heating carbonization temperature is 700° C.-1000° C., and the insulation time is 2-5 hours.

[0026] In step 4), the oxidizing atmosphere is selected from at least one of carbon dioxide, oxygen, water vapor or flue gas; the heating activation temperature is 800° C.-1100° C., and the insulation time is 1-6 hours.

[0027] In step 5), the non-oxidizing atmosphere is selected from at least one of nitrogen, argon, hydrogen or helium; the silicon-containing compound gas is selected from at least one of monosilane, disilane, trichlorosilane and silicon tetrachloride; the siliconizing treatment is a vapor deposition treatment, the deposition temperature is 400°C to 600°C, and the deposition time is 4-16h; the carbon source gas is selected from at least one of methane, ethylene, acetylene, cyclohexane, petroleum gas, propane, benzene and toluene; the temperature during the carbon coating treatment is 540°C to 700°C, and the carbon coating treatment time is 0.5-10h.

[0028] If necessary, a secondary carbon coating step may be added after step 5) and before step 6): the carbon-coated body is placed in a horizontal rotary kiln, and a carbon source gas is introduced in a non-oxidizing atmosphere for secondary carbon coating.

[0029] The carbon source gas used for the above-mentioned secondary carbon coating is selected from at least one of methane, ethylene, acetylene, cyclohexane, petroleum gas, propane, benzene and toluene; the temperature of the secondary carbon coating is 540°C-700°C, and the secondary carbon coating time is 3-10 hours; the non-oxidizing atmosphere is selected from at least one of nitrogen, argon, hydrogen or helium.

[0030] The present invention also provides a lithium ion battery negative electrode, which comprises the above-mentioned silicon-carbon negative electrode material with a gradient silicon concentration distribution for lithium ion batteries, or comprises the silicon-carbon negative electrode material with a gradient silicon concentration distribution for lithium ion batteries prepared using the above-mentioned method for preparing the silicon-carbon negative electrode material with a gradient silicon concentration distribution for lithium ion batteries.

[0031] The present invention also provides a lithium ion battery, which comprises the above-mentioned lithium ion battery negative electrode.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. In the silicon-carbon negative electrode material with gradient silicon concentration of the present invention, the inner core porous carbon is a microporous structure, and the outer layer porous carbon is a mesoporous structure. When silane is deposited, the mesoporous structure will not block the pores, and the micropores have a strong adsorption force. Nano-silicon is more easily deposited in the micropores of the inner core porous carbon, and the mesopores of the outer layer porous carbon simultaneously adsorb silane and deposit nano-silicon, which greatly improves the pore volume utilization rate of the porous carbon;

[0034] 2. During silane deposition, a large amount of nano-silicon is deposited on the inner core porous carbon, effectively avoiding the formation of a thick silicon shell on the surface of the material; the outer porous carbon acts as a buffer layer, effectively preventing the electrolyte from directly contacting the active material silicon to produce side reactions. In a silicon-rich system, the mesopores of the outer porous carbon can effectively buffer the volume expansion;

[0035] 3. The surface of the silicon-carbon negative electrode material of the present invention is a dense carbon coating layer, which can effectively isolate the contact between the active material and the electrolyte, prevent the occurrence of side reactions, and improve the cycle performance of the battery;

[0036] 4. The metal ash in the silicon-carbon negative electrode material of the present invention can improve the conductivity of the material and serve as an electrochemical active site to provide a fast transmission channel for lithium ions and improve the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic structural diagram of the silicon-carbon negative electrode material with a gradient silicon concentration distribution of the present invention;

[0038] Figure 2 The X-ray diffraction (XRD) pattern of the silicon-carbon negative electrode material prepared in Example 1;

[0039] Figure 3 This is a scanning electron microscope (SEM) photograph of the silicon-carbon negative electrode material prepared in Example 1;

[0040] Figure 4 The first cycle voltage capacity curve of the battery of the silicon-carbon negative electrode material prepared in Example 1;

[0041] Figure 5 The charging specific capacity and capacity retention rate curves of the battery with silicon-carbon negative electrode material prepared in Example 1 in the first 10 cycles. DETAILED DESCRIPTION

[0042] The present invention will now be further described in detail by way of embodiments in conjunction with the accompanying drawings, but the present invention is not limited to the embodiments.

[0043] Example 1

[0044] 1) Weigh 62g of resorcinol, 46g of terephthalaldehyde and 1g of aluminum chloride respectively, dissolve them in 1500g of deionized water, stir evenly, and heat at 40°C for 5h to obtain a metal ash-doped precursor phenolic resin seed. Then add 370g of formaldehyde, 6g of aluminum chloride, 70g of sodium hydroxide, 10g of polyvinyl pyrrolidone and 190g of phenol solution to the above solution in sequence, stir evenly, and heat at 90°C for 12h to obtain a metal ash-doped core-shell structure phenolic resin with a layer of metal ash-doped phenolic resin shell layer coated on the surface of the original metal ash-doped precursor phenolic resin seed. 2) The above core-shell structure phenolic resin is first dried at 100°C for 12h in a nitrogen atmosphere for heat curing treatment to obtain a cured body. 3) The cured body is kept at 900°C for 3h in a nitrogen atmosphere for carbonization treatment to obtain a carbonized body. 4) The carbonized body is activated at 900°C for 3 hours under a carbon dioxide atmosphere to obtain an activated body (i.e., hierarchical porous carbon). 5) 1 kg of the activated body is placed in a vertical fluidized bed reactor, and monosilane gas is introduced with nitrogen as the carrier gas, and the nitrogen flow rate is controlled to be 20L / min, and the monosilane flow rate is 2L / min. Siliconization treatment (vapor deposition treatment) is carried out at 500°C for 460 minutes to obtain a silicon-carbon composite. After that, acetylene gas is continued to be introduced with nitrogen as the carrier gas, and the acetylene gas flow rate is controlled to be 4L / min. Carbon coating treatment is carried out at 540°C for 10 hours to form a densely structured carbon layer (coating layer) with a thickness of 180nm on the surface of the material to obtain a carbon coating. 6) The obtained carbon coating is screened and demagnetized to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

[0045] That is, a silicon-carbon negative electrode material having a gradient silicon concentration distribution such as Figure 1 As shown, it includes graded porous carbon, nano-silicon and a coating layer 3, the graded porous carbon includes an inner core porous carbon 1 and an outer layer porous carbon 2, the pores of the inner core porous carbon 1 are micropores, the pores of the outer layer porous carbon 2 are mesopores 4, the nano-silicon is gradiently distributed on the graded porous carbon to form a silicon-carbon complex, and the silicon concentration in the mesopores 4 of the outer layer porous carbon 2 is less than the silicon concentration in the micropores of the inner core porous carbon 1; the coating layer 3 is a carbon layer, which is coated on the surface of the silicon-carbon complex.

[0046] The composition of silicon-carbon negative electrode materials was characterized by XRD test, such as Figure 2 As shown; the morphology of the silicon-carbon negative electrode material was characterized by SEM testing, as shown Figure 3 As shown. The specific surface area, pore size distribution and pore volume of the material were tested by nitrogen adsorption and desorption instrument. The specific surface area of ​​the above graded porous carbon is 1937m2 / g, and the pore volume is 0.91cm 3 / g, and the average pore size is 1.72nm. The specific surface area of ​​the above silicon-carbon negative electrode material is 2.1m2 / g. The powder resistivity of the material was tested by the ST2742B automatic powder resistivity tester, and the powder resistivity of the above silicon-carbon negative electrode material was 2.13Ω·cm. The median particle size of the silicon-carbon negative electrode material was measured to be 8.1μm by the Bettersize2600 laser particle size analyzer, and the mass ratio of nano-silicon in the silicon-carbon negative electrode material was 53.7% by the ELEMENTRAC CS-i carbon-sulfur analyzer.

[0047] The above-mentioned silicon-carbon negative electrode material with a gradient silicon concentration distribution, conductive carbon black and sodium carboxymethyl cellulose are mixed in a weight ratio of 70:15:15 to form a homogeneous slurry, and then coated on a copper foil. Subsequently, the copper foil was dried at room temperature for 30 minutes, and then dried at 110°C under vacuum for 4 hours to obtain a silicon-carbon negative electrode plate. The electrochemical properties of the electrode were evaluated using a half-cell (CR2016 button type) assembled in an argon-filled glove box. The button cell uses a silicon-carbon negative electrode plate as the working electrode, a lithium metal foil as the counter electrode, and a separator and an electrolyte. The LAND charge and discharge tester was used to perform charge and discharge tests on the above-assembled battery, with a charge and discharge range of 1mV to 2V, thereby obtaining a first efficiency of 93.5% for the half-cell, a first-cycle reversible specific capacity of 1961.1mAh / g, and a capacity retention rate of 84.6% after 10 charge and discharge cycles. Figure 4-Figure 5 shown.

[0048] The following examples and comparative examples were subjected to the same performance test.

[0049] Example 2

[0050] 1) Weigh 90g of phloroglucinol, 90g of benzaldehyde and 1.3g of aluminum chloride respectively and dissolve them in 1500g of deionized water, stir evenly, and heat at 50°C for 3h to obtain a metal ash-doped precursor phenolic resin seed. Then add 840g of acetaldehyde, 7.8g of aluminum chloride, 80g of ammonia water, 3.5g of sodium carboxymethyl cellulose and 350g of phenol solution to the above solution in sequence, stir evenly, and heat at 100°C for 10h to obtain a metal ash-doped core-shell structure phenolic resin with a layer of metal ash-doped phenolic resin shell layer coated on the surface of the original metal ash-doped precursor phenolic resin seed. 2) The above core-shell structure phenolic resin is first dried at 250°C for 15h in an argon atmosphere for heat curing treatment to obtain a cured body. 3) The cured body is kept at 1000°C for 2h in an argon atmosphere for carbonization treatment to obtain a carbonized body. 4) The carbonized body is activated at 1000°C for 4 hours under a carbon dioxide atmosphere to obtain an activated body (i.e., hierarchical porous carbon). 5) 1 kg of the activated body is placed in a vertical fluidized bed reactor, and monosilane gas is introduced with argon as the carrier gas, and the argon flow rate is controlled to be 20L / min, and the monosilane flow rate is 2L / min. The siliconization treatment (vapor deposition treatment) is carried out at 550°C for 600 minutes to obtain a silicon-carbon composite. After that, acetylene gas is continued to be introduced with argon as the carrier gas, and the acetylene gas flow rate is controlled to be 4L / min. The carbon coating treatment is carried out at 600°C for 5 hours to form a densely structured carbon layer (coating layer) with a thickness of 50nm on the surface of the material to obtain a carbon coating body. 6) The obtained carbon coating body is screened and demagnetized to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

[0051] The measured specific surface area of ​​the hierarchical porous carbon is 2345 m2 / g and the pore volume is 2.1 cm 3 / g, the average pore size is 2nm. The specific surface area of ​​the silicon-carbon negative electrode material is 2.3m2 / g, the powder resistivity is 6.72Ω·cm, the median particle size is 10μm, and the mass ratio of nano-silicon is 55%.

[0052] The measured first efficiency of the half-cell is 92.7%, the first-cycle reversible specific capacity is 2017.2 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 84.2%.

[0053] Example 3

[0054] 1) Weigh 50g of resorcinol, 37g of terephthalaldehyde and 0.45g of sodium chloride respectively and dissolve them in 1500g of deionized water, stir evenly, and heat at 25°C for 7h to obtain a metal ash-doped precursor phenolic resin seed. Then add 124g of formaldehyde, 2.5g of sodium chloride, 30g of sodium hydroxide, 3.8g of polyvinyl pyrrolidone and 64g of phenol solution to the above solution in sequence, stir evenly, and heat at 70°C for 14h to obtain a metal ash-doped core-shell structure phenolic resin with a layer of metal ash-doped phenolic resin shell layer coated on the surface of the original metal ash-doped precursor phenolic resin seed. 2) The above core-shell structure phenolic resin is first dried at 200°C for 18h in a nitrogen atmosphere for heat curing treatment to obtain a cured body. 3) The cured body is kept at 700°C for 5h in a nitrogen atmosphere for carbonization treatment to obtain a carbonized body. 4) Activate the carbonized body at 800°C in a carbon dioxide atmosphere for 4 hours to obtain an activated body (i.e., hierarchical porous carbon). 5) Take 1 kg of the activated body and place it in a vertical fluidized bed reactor. Use nitrogen as a carrier gas to pass monosilane gas, control the nitrogen flow rate to 20L / min, and the monosilane flow rate to 3L / min. Keep it at 600°C for 240 minutes to perform siliconization treatment (vapor deposition treatment) to obtain a silicon-carbon composite. After that, continue to pass acetylene gas with nitrogen as a carrier gas, control the acetylene gas flow rate to 4L / min, and perform carbon coating treatment at 600°C for 3 hours to form a densely structured carbon layer (coating layer) with a thickness of 200nm on the surface of the material to obtain a carbon coating. 6) The obtained carbon coating is screened and demagnetized to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

[0055] The specific surface area of ​​the hierarchical porous carbon was measured to be 1032 m2 / g and the pore volume was 0.5 cm 3 / g, the average pore size is 1nm. The specific surface area of ​​the silicon-carbon negative electrode material is 1.4m2 / g, the powder resistivity is 1.04Ω·cm, the median particle size is 5.4μm, and the mass ratio of nano-silicon is 45%.

[0056] The measured first efficiency of the half-cell is 93.9%, the first-cycle reversible specific capacity is 1700.5 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 83.7%.

[0057] Example 4

[0058] 1) Weigh 100g of resorcinol, 80g of terephthalaldehyde and 2.1g of aluminum chloride respectively and dissolve them in 1500g of deionized water, stir evenly, and heat at 50°C for 3h to obtain a metal ash-doped precursor phenolic resin seed. Then add 234g of formaldehyde, 4.8g of aluminum chloride, 43g of sodium hydroxide, 12g of dioctadecyl dimethyl ammonium chloride and 120g of phenol solution to the above solution in sequence, stir evenly, and heat at 70°C for 14h to obtain a metal ash-doped core-shell structure phenolic resin with a layer of metal ash-doped phenolic resin shell layer coated on the surface of the original metal ash-doped precursor phenolic resin seed. 2) The above core-shell structure phenolic resin is first dried at 160°C for 20h in a nitrogen atmosphere for heat curing treatment to obtain a cured body. 3) The cured body is carbonized at 900°C for 3h in a nitrogen atmosphere to obtain a carbonized body. 4) The carbonized body is activated at 1100°C for 1h in a water vapor atmosphere to obtain an activated body (i.e., hierarchical porous carbon). 5) 1kg of the activated body is placed in a vertical fluidized bed reactor, and monosilane gas is introduced with nitrogen as the carrier gas, and the nitrogen flow rate is controlled to be 20L / min, and the monosilane flow rate is 1L / min. Siliconization treatment (vapor deposition treatment) is carried out at 400°C for 960min to obtain a silicon-carbon composite. Afterwards, acetylene gas is continued to be introduced with nitrogen as the carrier gas, and the acetylene gas flow rate is controlled to be 4L / min. Carbon coating treatment is carried out at 650°C for 6h to form a densely structured carbon layer (coating layer) with a thickness of 80nm on the surface of the material to obtain a carbon coating. 6) The obtained carbon coating is screened and demagnetized to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

[0059] The specific surface area of ​​the hierarchical porous carbon was measured to be 2486 m2 / g and the pore volume was 2.5 cm 3 / g, the average pore size is 2.5nm. The specific surface area of ​​the silicon-carbon negative electrode material is 1.8m2 / g, the powder resistivity is 9.85Ω·cm, the median particle size is 9.2μm, and the mass ratio of nano-silicon is 57%.

[0060] The measured first efficiency of the half-cell is 94%, the first-cycle reversible specific capacity is 2049.5 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 83.2%.

[0061] Example 5

[0062] 1) Weigh 70g of aminophenol, 21g of formaldehyde and 0.86g of copper sulfate respectively and dissolve them in 1500g of deionized water, stir evenly, and heat at 25°C for 7h to obtain a metal ash-doped precursor phenolic resin seed. Then add 636g of formaldehyde, 13g of copper sulfate, 150g of hexadecyltrimethylammonium bromide, 15g of polyvinyl alcohol and 350g of phenol solution to the above solution in turn, stir evenly, and heat at 100°C for 10h to obtain a metal ash-doped core-shell structure phenolic resin with a layer of metal ash-doped phenolic resin shell layer coated on the surface of the original metal ash-doped precursor phenolic resin seed. 2) The above core-shell structure phenolic resin is first dried at 300°C for 10h in a nitrogen atmosphere for heat curing treatment to obtain a cured body. 3) The cured body is carbonized at 800°C for 4h in a nitrogen atmosphere to obtain a carbonized body. 4) The carbonized body is activated at 900°C for 6 hours in a water vapor atmosphere to obtain an activated body (i.e., hierarchical porous carbon). 5) 1 kg of the activated body is placed in a vertical fluidized bed reactor, and monosilane gas is introduced using nitrogen as a carrier gas, and the nitrogen flow rate is controlled to be 20 L / min, and the monosilane flow rate is 2 L / min. The body is kept at 500°C for 400 minutes for siliconization treatment (vapor deposition treatment) to obtain a silicon-carbon composite. After that, acetylene gas is continued to be introduced using nitrogen as a carrier gas, and the acetylene gas flow rate is controlled to be 4 L / min. The carbon coating treatment is performed at 700°C for 0.5 hours to form a densely structured carbon layer (coating layer) with a thickness of 10 nm on the surface of the material to obtain a carbon coating body as a primary carbon coating body. Afterwards, the obtained primary carbon coating body is put into a horizontal rotary furnace, acetylene gas is introduced with nitrogen as carrier gas, the nitrogen flow rate is controlled to be 5L / min, and the acetylene gas flow rate is controlled to be 2L / min, and a secondary carbon coating treatment is performed at 540°C for 3h to obtain a secondary carbon coating body. 6) The obtained secondary carbon coating body is screened and demagnetized to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

[0063] The specific surface area of ​​the hierarchical porous carbon was measured to be 1753 m2 / g and the pore volume was 0.82 cm 3 / g, the average pore size is 1.6nm. The specific surface area of ​​the silicon-carbon negative electrode material is 1.5m2 / g, the powder resistivity is 1.58Ω·cm, the median particle size is 7.8μm, and the mass ratio of nano-silicon is 50.2%.

[0064] The measured first efficiency of the half-cell is 92.3%, the first-cycle reversible specific capacity is 1814.3 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 84.3%.

[0065] Example 6

[0066] 1) Weigh 62g of resorcinol, 46g of terephthalaldehyde and 1.2g of aluminum chloride respectively and dissolve them in 1500g of deionized water, stir evenly, and heat at 45°C for 5h to obtain a metal ash-doped precursor phenolic resin seed. Then add 800g of benzaldehyde, 4.7g of aluminum chloride, 55g of sodium hydroxide, 8g of polyvinyl pyrrolidone and 160g of phenol solution to the above solution in sequence, stir evenly, and heat at 80°C for 12h to obtain a metal ash-doped core-shell structure phenolic resin with a layer of metal ash-doped phenolic resin shell layer coated on the surface of the original metal ash-doped precursor phenolic resin seed. 2) The above core-shell structure phenolic resin is first dried at 250°C for 15h in a nitrogen atmosphere for heat curing treatment to obtain a cured body. 3) The cured body is kept at 900°C for 2h in a nitrogen atmosphere for carbonization treatment to obtain a carbonized body. 4) The carbonized body is activated at 900°C for 2 hours under a carbon dioxide atmosphere to obtain an activated body (i.e., hierarchical porous carbon). 5) 1 kg of the activated body is placed in a vertical fluidized bed reactor, and monosilane gas is introduced with nitrogen as the carrier gas, and the nitrogen flow rate is controlled to be 20L / min, and the monosilane flow rate is 2L / min. Siliconization treatment (vapor deposition treatment) is carried out at 450°C for 490 minutes to obtain a silicon-carbon composite. After that, acetylene gas is continued to be introduced with nitrogen as the carrier gas, and the acetylene gas flow rate is controlled to be 4L / min. Carbon coating treatment is carried out at 600°C for 5 hours to form a densely structured carbon layer (coating layer) with a thickness of 200nm on the surface of the material to obtain a carbon coating. 6) The obtained carbon coating is screened and demagnetized to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

[0067] The specific surface area of ​​the hierarchical porous carbon was measured to be 2235 m2 / g and the pore volume was 0.97 cm 3 / g, the average pore size is 1.93nm. The specific surface area of ​​the silicon-carbon negative electrode material is 1.7m2 / g, the powder resistivity is 3.24Ω·cm, the median particle size is 6.5μm, and the mass ratio of nano-silicon is 54.9%.

[0068] The measured first efficiency of the half-cell is 94.7%, the first-cycle reversible specific capacity is 1999.4 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 83.5%.

[0069] Example 7

[0070] 1) Weigh 50g of phloroglucinol, 46g of terephthalaldehyde and 0.45g of sodium chloride respectively and dissolve them in 1500g of deionized water, stir evenly, and heat at 40°C for 5h to obtain a metal ash-doped precursor phenolic resin seed. Then add 620g of acetaldehyde, 3.1g of sodium chloride, 90g of hexadecyltrimethylammonium bromide, 12g of polyvinylpyrrolidone and 220g of phenol solution to the above solution in sequence, stir evenly, and heat at 90°C for 12h to obtain a metal ash-doped core-shell structure phenolic resin with a layer of metal ash-doped phenolic resin shell layer coated on the surface of the original metal ash-doped precursor phenolic resin seed. 2) The above core-shell structure phenolic resin is first dried at 100°C for 24h in a nitrogen atmosphere for heat curing treatment to obtain a cured body. 3) The cured body is carbonized at 900°C for 3h in a nitrogen atmosphere to obtain a carbonized body. 4) The carbonized body is activated at 900°C for 3.5 hours under a carbon dioxide atmosphere to obtain an activated body (i.e., hierarchical porous carbon). 5) 1 kg of the activated body is placed in a vertical fluidized bed reactor, and monosilane gas is introduced with nitrogen as the carrier gas, and the nitrogen flow rate is controlled to be 20L / min, and the monosilane flow rate is 2L / min. Siliconization treatment (vapor deposition treatment) is carried out at 550°C for 440 minutes to obtain a silicon-carbon composite. After that, acetylene gas is continued to be introduced with nitrogen as the carrier gas, and the acetylene gas flow rate is controlled to be 4L / min. Carbon coating treatment is carried out at 580°C for 8 hours to form a densely structured carbon layer (coating layer) with a thickness of 120nm on the surface of the material to obtain a carbon coating. 6) The obtained carbon coating is screened and demagnetized to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

[0071] The specific surface area of ​​the graded porous carbon was measured to be 1945 m2 / g and the pore volume was 0.93 cm 3 / g, the average pore size is 1.71nm. The specific surface area of ​​the silicon-carbon negative electrode material is 2m2 / g, the powder resistivity is 1.38Ω·cm, the median particle size is 9.2μm, and the mass ratio of nano-silicon is 52.4%.

[0072] The measured first efficiency of the half-cell is 92.8%, the first-cycle reversible specific capacity is 1906.7 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 84%.

[0073] Comparative Example 1

[0074] Other conditions and operations are the same as those in Example 1, except that after step 4), the metal ash-doped graded porous carbon is subjected to an acid wash treatment by immersing it in a 2 mol / L hydrochloric acid aqueous solution for 24 hours to remove the metal elements in the graded porous carbon, and then drying it at 120° C. in vacuum.

[0075] The specific surface area of ​​the hierarchical porous carbon was measured to be 1933 m2 / g and the pore volume was 0.91 cm 3 / g, the average pore size is 1.72nm. The specific surface area of ​​the silicon-carbon negative electrode material is 2.1m2 / g, the powder resistivity is 9.13Ω·cm, the median particle size is 8.1μm, and the mass ratio of nano-silicon is 55.1%.

[0076] The measured first efficiency of the half-cell is 90.1%, the first-cycle reversible specific capacity is 1900.4 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 81.3%.

[0077] Comparative Example 2

[0078] 1) Weigh 1200g of benzaldehyde, 2.2g of copper sulfate, 90g of sodium hydroxide, 15g of polyvinyl pyrrolidone and 250g of phenol solution respectively, add them into 1500g of deionized water in turn, stir evenly, and heat at 90°C for 12h to obtain a metal ash-doped phenolic resin. 2) The above-mentioned metal ash-doped phenolic resin is first dried at 300°C for 10h in a nitrogen atmosphere for heat curing to obtain a solidified body. 3) The solidified body is kept at 1000°C for 2h in a nitrogen atmosphere for carbonization treatment to obtain a carbonized body. 4) The carbonized body is activated at 900°C for 3h in a carbon dioxide atmosphere for activation treatment to obtain an activated body (i.e., porous carbon, equivalent to the inner core of the hierarchical porous carbon). 5) Take 1kg of the activated body and place it in a vertical fluidized bed reactor, introduce monosilane gas with nitrogen as carrier gas, control the nitrogen flow rate to 20L / min, and the monosilane flow rate to 2L / min, keep warm at 500℃ for 490min, then continue to introduce acetylene gas with nitrogen as carrier gas, control the acetylene gas flow rate to 4L / min, and perform carbon coating treatment at 600℃ for 5h to obtain a carbon coating body, as a primary carbon coating body, due to the floating silicon on the porous carbon surface, the thickness of the surface coated carbon layer is uneven. Afterwards, the obtained primary carbon coating body is put into a horizontal rotary kiln, introduce acetylene gas with nitrogen as carrier gas, control the nitrogen flow rate to 5L / min, control the acetylene gas flow rate to 2L / min, and perform secondary carbon coating treatment at 600℃ for 6h to obtain a secondary carbon coating body. 6) The obtained secondary carbon coating body is screened and demagnetized to obtain a silicon-carbon negative electrode material.

[0079] The specific surface area of ​​the porous carbon was measured to be 2298 m2 / g and the pore volume was 0.98 cm 3 / g, the average pore size is 1.97nm. The specific surface area of ​​the primary carbon coating is 68m2 / g, and the powder resistivity is 51.62Ω·cm. The specific surface area of ​​the silicon-carbon negative electrode material is 9.8m2 / g, the median particle size is 7.7μm, and the mass ratio of nano-silicon is 54.8%.

[0080] The measured first efficiency of the half-cell is 88.5%, the first-cycle reversible specific capacity is 1887.1 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 78.2%.

[0081] Comparative Example 3

[0082] 1) Weigh 480g of formaldehyde, 8g of aluminum chloride, 90g of sodium hydroxide, 15g of polyvinyl pyrrolidone and 250g of phenol solution respectively, add them into 1500g of deionized water in turn, stir evenly, and heat at 90°C for 12h to obtain a metal ash-doped phenolic resin. 2) The above-mentioned metal ash-doped phenolic resin is first dried at 200°C for 18h in a nitrogen atmosphere for heat curing treatment to obtain a solidified body. 3) The solidified body is kept at 900°C for 3h in a nitrogen atmosphere for carbonization treatment to obtain a carbonized body. 4) The carbonized body is activated at 900°C for 3h in a carbon dioxide atmosphere for activation treatment to obtain an activated body (i.e., porous carbon, equivalent to the outer layer of hierarchical porous carbon). 5) Take 1kg of porous carbon and place it in a vertical fluidized bed reactor, introduce monosilane gas with nitrogen as carrier gas, control the nitrogen flow rate to 20L / min, and the monosilane flow rate to 2L / min, keep warm at 500℃ for 490min, then continue to introduce acetylene gas with nitrogen as carrier gas, control the acetylene gas flow rate to 4L / min, and perform carbon coating treatment at 600℃ for 5h to obtain a carbon coating body, as a primary carbon coating body, due to the floating silicon on the surface of the porous carbon, the thickness of the surface coated carbon layer is uneven. Afterwards, the obtained primary carbon coating body is put into a horizontal rotary kiln, and acetylene gas is introduced with nitrogen as carrier gas, and the nitrogen flow rate is controlled to 5L / min, and the acetylene gas flow rate is controlled to 2L / min, and a secondary carbon coating treatment is performed at 560℃ for 10h to obtain a secondary carbon coating body. 6) The obtained secondary carbon coating body is screened and demagnetized to obtain a silicon-carbon negative electrode material.

[0083] The specific surface area of ​​the porous carbon was measured to be 1467 m2 / g and the pore volume was 0.72 cm 3 / g, the average pore size is 8.21nm. The specific surface area of ​​the primary carbon coating is 88.7m2 / g, and the powder resistivity is 80.27Ω·cm. The specific surface area of ​​the silicon-carbon negative electrode material is 8.3m2 / g, the median particle size is 7.8μm, and the mass ratio of nano-silicon is 55.2%.

[0084] The measured first efficiency of the half-cell is 87.8%, the first-cycle reversible specific capacity is 1876.3 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 77.5%.

[0085] Comparative Example 4

[0086] 1) Weigh 62g of resorcinol and 46g of terephthalaldehyde respectively and dissolve them in 1500g of deionized water, stir evenly, and heat at 40°C for 5h to obtain a precursor phenolic resin seed. Then add 370g of formaldehyde, 70g of sodium hydroxide, 10g of polyvinyl pyrrolidone and 190g of phenol solution to the above solution in turn, stir evenly, and heat at 90°C for 12h to obtain a core-shell structure phenolic resin. 2) The above core-shell structure phenolic resin is first dried at 100°C for 12h in a nitrogen atmosphere for heat curing treatment to obtain a cured body. 3) Carbonize the mixture at 900°C for 3h in a nitrogen atmosphere to obtain a carbonized body. 4) Activate the mixture at 900°C for 3h in a carbon dioxide atmosphere to obtain an activated body (i.e., hierarchical porous carbon). 5) Take 1kg of the activated body and place it in a vertical fluidized bed reactor, introduce monosilane gas with nitrogen as carrier gas, control the nitrogen flow rate to 20L / min, and the monosilane flow rate to 2L / min, and keep it at 500℃ for 460min for siliconization treatment (vapor deposition treatment), then continue to introduce acetylene gas with nitrogen as carrier gas, control the acetylene gas flow rate to 4L / min, and perform carbon coating treatment at 540℃ for 10h to obtain a carbon coating body, as a primary carbon coating body, due to the floating silicon on the porous carbon surface, the thickness of the surface coating carbon layer is uneven. Afterwards, the obtained primary carbon coating body is put into a horizontal rotary kiln, and acetylene gas is introduced with nitrogen as carrier gas, and the nitrogen flow rate is controlled to 5L / min, and the acetylene gas flow rate is controlled to 2L / min, and a secondary carbon coating treatment is performed at 700℃ for 8h to obtain a secondary carbon coating body. 6) The obtained secondary carbon coating body is screened and demagnetized to obtain a silicon-carbon negative electrode material.

[0087] The specific surface area of ​​the hierarchical porous carbon was measured to be 1180 m2 / g and the pore volume was 0.58 cm 3 / g, the average pore size is 1.5nm. The specific surface area of ​​the primary carbon coating is 113m2 / g, and the powder resistivity is 100.59Ω·cm. The specific surface area of ​​the silicon-carbon negative electrode material is 8.7m2 / g, the median particle size is 8.4μm, and the mass ratio of nano-silicon is 54.7%.

[0088] The measured first efficiency of the half-cell is 86.1%, the first-cycle reversible specific capacity is 1850.1 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 77%.

[0089] Comparative Example 5

[0090] 1) Weigh 62g of resorcinol, 46g of terephthalaldehyde and 2g of aluminum chloride respectively, dissolve them in 1500g of deionized water, stir evenly, and heat at 45°C for 5h to obtain a metal ash-doped precursor phenolic resin seed. Then add 370g of formaldehyde, 1.2g of aluminum chloride, 70g of sodium hydroxide, 10g of polyvinyl pyrrolidone and 190g of phenol solution to the above solution in turn, stir evenly, and heat at 100°C for 12h to obtain a metal ash-doped core-shell structure phenolic resin. 2) The above core-shell structure phenolic resin is first dried at 100°C for 24h in a nitrogen atmosphere for curing treatment to obtain a cured body. 3) Carbonize the mixture at 900°C for 3h in a nitrogen atmosphere to obtain a carbonized body. 4) Activate the mixture at 650°C for 7h in a carbon dioxide atmosphere to obtain an activated body (i.e., hierarchical porous carbon). 5) Take 1kg of hierarchical porous carbon and place it in a vertical fluidized bed reactor, introduce monosilane gas with nitrogen as carrier gas, control the nitrogen flow rate to 20L / min, and the monosilane flow rate to 2L / min, keep warm at 500℃ for 490min, then continue to introduce acetylene gas with nitrogen as carrier gas, control the acetylene gas flow rate to 4L / min, and perform carbon coating treatment at 600℃ for 5h to obtain a carbon coating body, as a primary carbon coating body, due to the floating silicon on the porous carbon surface, the thickness of the surface coating carbon layer is uneven. Afterwards, the obtained primary carbon coating body is put into a horizontal rotary kiln, introduce acetylene gas with nitrogen as carrier gas, control the nitrogen flow rate to 5L / min, control the acetylene gas flow rate to 2L / min, and perform secondary carbon coating treatment at 650℃ for 7h to obtain a secondary carbon coating body. 6) The obtained secondary carbon coating body is screened and demagnetized to obtain a silicon-carbon negative electrode material.

[0091] The specific surface area of ​​the hierarchical porous carbon was measured to be 2200 m2 / g and the pore volume was 1.9 cm 3 / g, the average pore size is 1.73nm. The specific surface area of ​​the primary carbon coating is 97.6m2 / g, and the powder resistivity is 84.53Ω·cm. The specific surface area of ​​the silicon-carbon negative electrode material is 6.5m2 / g, the median particle size is 7.9μm, and the mass ratio of nano-silicon is 55%.

[0092] The measured first efficiency of the half-cell is 88.3%, the first-cycle reversible specific capacity is 1882.3 mAh / g, and the capacity retention rate after 10 charge and discharge cycles is 77.2%.

[0093] Embodiments 1-7 are silicon-carbon negative electrode materials with gradient silicon concentration distribution. The BET and resistance after vapor deposition carbon coating are both small, which shows that the hierarchical porous carbon structure of embodiments 1-7 can effectively limit nano silicon mainly to the porous carbon core, and no silicon shell is formed on the porous carbon surface, and the carbon layer is easy to coat, and the electrochemical performance is also good. The silicon-carbon negative electrode material of comparative examples 2-5 (wherein the mass of the metal salt continued to be added when preparing the core-shell structure phenolic resin in comparative example 5 is lower than the mass of the metal salt added when preparing the precursor phenolic resin seed) produces a larger BET and resistance after vapor deposition carbon coating, which shows that the internal pore utilization rate of the porous carbon structure of comparative examples 2-5 is low, and silicon shells are formed on the surface, and the carbon layer is not easy to coat, even after secondary carbon coating, its electrochemical performance is also reduced. In addition, although no floating silicon is formed on the hierarchical porous carbon surface of comparative example 1, its electrochemical performance is lower than that of embodiment 1, which reflects the improvement of the battery performance of silicon-carbon negative electrode material by metal doping.

[0094] The above-mentioned technologies not specifically mentioned are all referred to the prior art.

[0095] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.

Claims

1. A silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries, characterized in that: It includes graded porous carbon, nano-silicon and a coating layer. The graded porous carbon includes an inner core porous carbon and an outer layer porous carbon. The pores of the inner core porous carbon are micropores, and the pores of the outer layer porous carbon are mesopores. Nano-silicon is distributed on the graded porous carbon in a gradient manner to form a silicon-carbon complex. The silicon concentration in the mesopores of the outer layer porous carbon is less than the silicon concentration in the micropores of the inner core porous carbon. The coating layer is a carbon layer, which is coated on the surface of the silicon-carbon complex.

2. The silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries according to claim 1, characterized in that: The carbon layer has a dense structure and a thickness of 10~200nm.

3. The silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries according to claim 1, characterized in that: The median particle size of the silicon-carbon negative electrode material is 5-10 μm, the specific surface area is 1-20 m² / g, the powder resistivity is 1-10 Ω·cm, and the mass ratio of nano-silicon is 45% to 57%.

4. The silicon-carbon negative electrode material with a gradient silicon concentration for lithium-ion batteries according to claim 1, characterized in that: The graded porous carbon has a pore volume of 0.5-2.5 cm³ / g, a specific surface area of ​​1000-2500 m² / g, and an average pore diameter of 1.0-2.5 nm.

5. The method for preparing a silicon-carbon negative electrode material having a gradient silicon concentration for a lithium ion battery according to any one of claims 1 to 4, comprising the following steps: 1) stirring an aqueous solution containing a phenolic monomer, an aldehyde monomer and a metal salt under heating conditions to obtain a metal ash-doped precursor phenolic resin seed; continuing to sequentially add an aldehyde monomer, a metal salt, an alkaline catalyst, a surfactant and a phenolic monomer to the aqueous solution, stirring and heating, to obtain a metal ash-doped core-shell structure phenolic resin in which a layer of a metal ash-doped phenolic resin shell layer is further coated on the surface of the original metal ash-doped precursor phenolic resin seed; The core-shell phenolic resin obtained in step 1) is heated and cured in a non-oxidizing atmosphere to obtain a cured product; 3) heating the solidified body obtained in step 2) in a non-oxidizing atmosphere to carbonize the solidified body to obtain a carbonized body; 4) heating and activating the carbonized body obtained in step 3) in an oxidizing atmosphere to obtain an activated body; 5) introducing a silicon-containing compound gas into the activated body obtained in step 4) in a non-oxidizing atmosphere to perform siliconization treatment to obtain a silicon-carbon composite body, and then introducing a carbon source gas to perform carbon coating treatment to obtain a carbon-coated body; 6) The carbon coating obtained in step 5) is screened and demagnetized to obtain a silicon-carbon negative electrode material with a gradient silicon concentration distribution.

6. The method for preparing a silicon-carbon negative electrode material having a gradient silicon concentration for a lithium-ion battery according to claim 5, characterized in that: In step 1), the phenolic monomer is selected from at least one of phenol, resorcinol, aminophenol, tannic acid, and phloroglucinol; The aldehyde monomer is at least one selected from formaldehyde, terephthalaldehyde, paraformaldehyde, polyoxymethylene, acetaldehyde, valeraldehyde, benzaldehyde, glutaraldehyde, salicylaldehyde, and furfural; The metal salt is at least one selected from soluble salts of alkali metals, alkaline earth metals and transition metals; When preparing the precursor phenolic resin seed, the heating temperature is 25°C to 50°C, the heating time is 3-7h, the mass ratio of the added phenolic monomer to the aldehyde monomer is 1-3.5, and the mass of the metal salt is less than 3% of the mass of the phenolic monomer; The alkaline catalyst is selected from at least one of ammonia water, p-phenylenediamine, ethylenediamine, hexamethylenediamine, sodium hydroxide, hexadecyltrimethylammonium bromide, and Bis-tris; The surfactant is selected from at least one of an ionic surfactant and a non-ionic surfactant; When preparing the core-shell structure phenolic resin, the heating temperature is 70°C-100°C, the heating time is 10-14h, the mass ratio of the phenolic monomer to the aldehyde monomer is 0.20-0.55, the mass ratio of the alkaline catalyst to the phenolic monomer is 0.2-0.5, the mass of the surfactant is 1%-10% of the mass of the phenolic monomer, and the mass of the metal salt is less than 4% of the mass of the phenolic monomer; the mass of the metal salt added when preparing the core-shell structure phenolic resin is higher than the mass of the metal salt added when preparing the precursor phenolic resin seed; In step 2), the non-oxidizing atmosphere is selected from at least one of nitrogen, argon, hydrogen or helium, the heating curing temperature is 100°C-300°C, and the holding time is 10-24h; In step 3), the non-oxidizing atmosphere is selected from at least one of nitrogen, argon, hydrogen or helium; the heating carbonization temperature is 700°C-1000°C, and the holding time is 2-5h; In step 4), the oxidizing atmosphere is selected from at least one of carbon dioxide, oxygen, water vapor or flue gas; the heating activation temperature is 800°C-1100°C, and the holding time is 1-6h; In step 5), the non-oxidizing atmosphere is selected from at least one of nitrogen, argon, hydrogen or helium; the silicon-containing compound gas is selected from at least one of monosilane, disilane, trichlorosilane and silicon tetrachloride; the siliconizing treatment is a vapor deposition treatment, the deposition temperature is 400°C~600°C, and the deposition time is 4-16h; the carbon source gas is selected from at least one of methane, ethylene, acetylene, cyclohexane, petroleum gas, propane, benzene and toluene; the temperature during the carbon coating treatment is 540°C-700°C, and the carbon coating treatment time is 0.5-10h.

7. The method for preparing a silicon-carbon negative electrode material having a gradient silicon concentration distribution for a lithium-ion battery according to claim 5 or 6, characterized in that: A secondary carbon coating step is added after step 5) and before step 6): the carbon-coated body is placed in a horizontal rotary kiln, and a carbon source gas is introduced in a non-oxidizing atmosphere for secondary carbon coating.

8. The method for preparing a silicon-carbon negative electrode material having a gradient silicon concentration distribution for a lithium-ion battery according to claim 7, characterized in that: The carbon source gas used for secondary carbon coating is selected from at least one of methane, ethylene, acetylene, cyclohexane, petroleum gas, propane, benzene and toluene; the temperature of secondary carbon coating is 540°C-700°C, and the secondary carbon coating time is 3-10 hours; the non-oxidizing atmosphere is selected from at least one of nitrogen, argon, hydrogen or helium.

9. A negative electrode for a lithium ion battery, characterized in that: A silicon-carbon negative electrode material with a gradient silicon concentration distribution for a lithium ion battery comprising any one of claims 1 to 4, or a silicon-carbon negative electrode material with a gradient silicon concentration distribution for a lithium ion battery prepared by the method for preparing a silicon-carbon negative electrode material with a gradient silicon concentration distribution for a lithium ion battery comprising any one of claims 5 to 8.

10. A lithium ion battery, characterized in that: A lithium-ion battery negative electrode comprising the negative electrode of claim 9.

Citation Information

Patent Citations

  • Silicon-carbon composite material with core-shell structure, preparation method of silicon-carbon composite material and secondary battery

    CN117766714A

  • Silicon-carbon composite material, negative plate and battery

    CN118213508A

  • Low-expansion silicon carbon adopting composite porous carbon as well as preparation method and application of low-expansion silicon carbon

    CN118825269A

  • Composite multilevel structure carbon material as well as preparation method and application thereof

    CN118841554A

Cited By

  • Silicon-carbon negative electrode material, preparation method thereof and secondary battery

    CN120690838A

  • Preparation method of high-structural-strength porous carbon for silicon-carbon negative electrode

    CN120736521A

  • Low-expansion porous silicon negative electrode material for solid-state battery and lithium-ion solid-state battery

    CN120878826A

  • Low-expansion and high-capacity silicon-carbon composite negative electrode material and preparation method thereof

    CN121405065A

  • Preparation method of silicon-carbon composite material for manufacturing silicon-carbon negative electrode plate

    CN121439756A